Multilocus species delimitation in the Crotalus triseriatus species group (Serpentes: Viperidae: Crotalinae), with the description of two new species - Bryson, Robert Jr. W.; Linkem, Charles W.; Dorcas, Michael E.; Lathrop, Amy; Jones, Jason M.; Alvarado-Díaz, Javier; Grünwald, Christoph I.; Murphy, Robert W. (Zootaxa, 2014)
Members of the Crotalus triseriatus species group of montane rattlesnakes are widely distributed across the highlands of Mexico and southwestern USA. Although five species are currently recognized within the group, species limits remain to be tested. Genetic studies suggest that species may be paraphyletic and that at least one cryptic species may be present. We generate 3,346 base pairs of DNA sequence data from seven nuclear loci to test competing models of species delimitation in the C. triseriatus group using Bayes factor delimitation. We also examine museum specimens from the Trans-Mexican Volcanic Belt for evidence of cryptic species. We find strong support for a nine-species model and genetic and morphological evidence for recognizing two new species within the group, which we formally describe here. Our results suggest that the current taxonomy of the C. triseriatus species group does not reflect evolutionary history. We suggest several conservative taxonomic changes to the group, but future studies are needed to better clarify relationships among species and examine genetic patterns and structure within wide-ranging lineages.